Ukraine : Report on the Observance of Standards and Codes - Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2004)
This paper reviews the Report on the Observance of Standards and Codes on Fiscal Transparency for Ukraine, and provides an assessment of fiscal transparency practices in Ukraine against the requirements of the IMF Code of Good Practices on Fiscal Transparency. It reviews the description of practice, prepared by the IMF staff on the basis of discussions with the authorities and their responses to the fiscal transparency questionnaire, and provides a commentary from IMF staff.